Maternal and Child Health Matters Around the World 2020
DOI: 10.5772/intechopen.80754
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelation of the Mother’s Health Status with the State of Health of First- and Second-Year-Old Children

Abstract: We evaluated the state of health of the mother and child at birth, and the probability of the diagnosis of cancelation in the child at the end of the second year of life. The sample consisted of 100 mother-child dyads. The complex assessment of the children's health status was based on the individual medical records. Mothers filled the questionnaire evaluating the mother's relation to her child during the first 2 years of life, and the questionnaire aimed at assessing the emotional intelligence level. Almost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Sumter et al [80] also state that adolescents perceive love and romance as encompassing passion, connection and physical intimacy. However, the literature suggests that love in the context of romantic relationships often renders adolescents vulnerable and encourages them to engage in sexual activities [69,81]. Furthermore, adolescents may underestimate the sexual risks they take and are highly likely to have unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sumter et al [80] also state that adolescents perceive love and romance as encompassing passion, connection and physical intimacy. However, the literature suggests that love in the context of romantic relationships often renders adolescents vulnerable and encourages them to engage in sexual activities [69,81]. Furthermore, adolescents may underestimate the sexual risks they take and are highly likely to have unprotected sex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adolescents may underestimate the sexual risks they take and are highly likely to have unprotected sex. A study that was conducted in India by Janardhana and Manjula [81] found that adolescent women who engaged in physical intimacy and premarital sex with a romantic partner thought that it would lead to a marriage proposal. A similar tendency was noted by Kyilleh et al [69], as Ghanaian adolescent women engaged in premarital sex with the expectation that their partners would marry them.…”
Section: Discussionmentioning
confidence: 99%
“…Among family members, the mother's personality and the way she communicates with the child are of fundamental importance (12). The child's behavioral problems in the early years of life are related to the mother's negative behavior and communication and her stress, and thus the child's problematic behavior causes unpleasant emotional reactions and a decrease in the mother's general health (13).…”
Section: Introductionmentioning
confidence: 99%
“…The health and development of a child are intrinsically linked to their mother's physical and mental well-being (1,2). Poor maternal mental health can adversely impact a range of pregnancy, birth, and child outcomes (3)(4)(5) such as higher risks of obstetric complications, preterm labour, fetal growth restrictions, low birth weight of the baby, delayed initiation of breastfeeding, and low quality of responsive caregiving (5).…”
Section: Introductionmentioning
confidence: 99%